A Research on Mormonism and the Mormon Church - Isik, Ramazan (Cumhuriyet Univ, Fac Theology, 2006)
The Mormon church which was found in 1930's by Joseph Smith is one of the new religious movements attached eclectic elements. Not only does it widespread in America but also in different parts of the world. In this article, the historical development process of the Mormon church, the church's organization, missionary activities, family and marriage have been studied.
Keywords: The Mormon Church; Joseph Smith; The Book of Mormon; God; Jesus Christ; Family; Plural Marriage and Missionary